Effect of Mg10Al2Nd Master Alloy on the Grain Refinement of Mg3Nd Alloy - WANG Lei; FENG Yi cheng; ZHAO Si cong; GUO Er jun; CHEN Yan hong; WANG Li ping (Journal of Harbin University of Science and Technology)
In this study, the grain refinement behavior of Mg10Al2Nd master alloy to Mg3Nd alloy was studied by optical microscope (OM), scanning electron microscope (SEM) and Xray diffraction (XRD) The experimental results showed that Mg10Al2Nd master alloy is composed of αMg and particle Al2Nd phases The addition of Mg10Al2Nd master alloy can refine Mg3Nd alloy, and the refining effect is enhanced as the content of Mg10Al2Nd increases By adding 20% Mg10Al2Nd, the grain size of Mg3Nd alloy was refined from 1242±135 μm to 173±19 μm The mechanism of grain refinement is the synergistic effect of solute effect and heterogeneous nucleation of Al2Nd